2005
DOI: 10.1021/jm049465g
|View full text |Cite
|
Sign up to set email alerts
|

Novel Heterocyclic Trans Olefin Analogues of N-{4-[4-(2,3-Dichlorophenyl)piperazin-1-yl]butyl}arylcarboxamides as Selective Probes with High Affinity for the Dopamine D3 Receptor

Abstract: Dopamine D3 receptor subtypes have been hypothesized to play a pivotal role in modulating the reinforcing and drug-seeking effects induced by cocaine. However, definitive pharmacological investigations have been hampered by the lack of highly D3 receptor selective compounds that can be used in vivo. To address this problem, the potent and D3-receptor-selective antagonist NGB 2904 (1, 9H-fluorene-2-carboxylic acid {4-[(2,3-dichlorophenyl)-piperazin-1-yl]-butyl}-amide, Ki (hD3) = 2.0 nM, Ki (hD2L) = 112 nM, D2/D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
200
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 117 publications
(204 citation statements)
references
References 20 publications
(55 reference statements)
4
200
0
Order By: Relevance
“…While the MEDs for the inhibition of yawning by PG01037 and SB-277011A (32.0 mg/kg for both) are slightly higher than those reported for SB-277011A on a variety of operant behaviors (3.0 -24 mg/kg; Andreoli et al 2003;Di Ciano et al 2003;Xi et al 2004;Gilbert et al 2005;Xi et al 2005;Cervo et al 2007) and are likewise higher than might be expected based on in vitro D3 affinities of 0.7 nM and 10.7 nM respectively Grundt et al 2005) there is no evidence to suggest that the inhibition of yawning by these antagonists results from anything other than an antagonist activity at the D3 receptor. Not only did PG01037 and SB-277011A not inhibit sumanirole-induced hypothermia or increase yawning induced by high doses of PD-128,907 in the current studies at doses up to 56.0 mg/ kg, but SB-277011A also failed to induce catalepsy and increases plasma prolactin levels at doses up to 78.8 and 93 mg/kg; p.o.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…While the MEDs for the inhibition of yawning by PG01037 and SB-277011A (32.0 mg/kg for both) are slightly higher than those reported for SB-277011A on a variety of operant behaviors (3.0 -24 mg/kg; Andreoli et al 2003;Di Ciano et al 2003;Xi et al 2004;Gilbert et al 2005;Xi et al 2005;Cervo et al 2007) and are likewise higher than might be expected based on in vitro D3 affinities of 0.7 nM and 10.7 nM respectively Grundt et al 2005) there is no evidence to suggest that the inhibition of yawning by these antagonists results from anything other than an antagonist activity at the D3 receptor. Not only did PG01037 and SB-277011A not inhibit sumanirole-induced hypothermia or increase yawning induced by high doses of PD-128,907 in the current studies at doses up to 56.0 mg/ kg, but SB-277011A also failed to induce catalepsy and increases plasma prolactin levels at doses up to 78.8 and 93 mg/kg; p.o.…”
Section: Discussionmentioning
confidence: 54%
“…Although several agonists and antagonists have been reported to be over 100-fold selective for either the D3 (e.g., Stemp et al 2000;Grundt et al 2005) or D2 (e.g., Vangveravong et al 2006) receptors based on in vitro binding studies, a large degree of variability exists with respect to the reported in vitro binding affinities and D2/D3 selectivity ratios. A variety of factors may account for these differences in affinity and selectivity including differences in receptor species, expression systems, radioligands, and/or assay conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Nafadotride, U99194, SB-277011A, and PG01037 have been shown to preferentially bind the D3 receptor over the D2 receptor in vitro, with D3 selectivities of approximately 3-, 30-, 100-, and 133-fold, respectively (Sautel et al, 1995;Audinot et al, 1998;Flietstra and Levant, 1998;Stemp et al, 2000;Grundt et al, 2005), and were used at behaviorally active doses (Waters et al, 1993;Vorel et al, 2002;Di Ciano et al, 2003, Leriche et al, 2003Millan et al, 2004) to examine their effects on yawning behavior in rats.…”
Section: D3-preferringmentioning
confidence: 99%
“…An early hypothesis regarding the biphasic regulation of apomorphine-induced yawning behavior attributed the induction of yawning behavior to a D2 agonist activity, whereas the inhibition seen at higher doses was thought to be due to a competing D1 agonist activation (Yamada and Furukawa, 1980;Urba-Holmgren et al, 1982). The cloning of the dopamine D3 receptor and the development of agonists such as PD-128,907 (Pugsley et al, 1995) and 7-OH-DPAT [(Ϯ)-7-hydroxy-2-dipropylaminotetralin HBr] (Levesque et al, 1992;Pugsley et al, 1995), as well as antagonists including U99194 (Cannon et al, 1982;Haadsma-Svensson and Svensson, 1998), SB-277011A (Reavill et al, 2000;Stemp et al, 2000), and PG01037 (Grundt et al, 2005) with greater degrees of in vitro selectivity for the D3 receptor have allowed greater insights into the regulation of dopaminergic agonist-induced yawning behavior to be made. Based on a series of studies examining the unconditioned behavioral effects of 7-OH-DPAT (Daly and Waddington, 1993;Ferrari and Giuliani, 1995;Kurashima et al, 1995), as well as binding studies (Levant et al, 1995), Levant (1997) hypothesized in an extensive review that D2/D3 agonist-induced yawning may be a D3 agonist-mediated effect, whereas the inhibition seen at higher doses was a result of concomitant D2 agonist activation.…”
mentioning
confidence: 99%
“…Retention of the C-4 piperidine sp3 carbon was previously reported to be preferred by the D2 receptor 12 and replacement of the 4-piperidinol function with other groups was explored (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). In general, none of these analogues showed higher affinity for D2 than the parent compound.…”
mentioning
confidence: 99%